ä½¿ç”¨äº¤é™…æ³•æé«˜å¦ç”Ÿçš„å£è¯èƒ½åŠ› ä»¥èµ¤é“ä½³è‚²åˆä¸äºŒå¹´çº§ä¸ºä¾‹ - Saminor, Yulius; Thamrin, Lily; ., Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
æ‘˜è¦ï¼šå£è¯æ˜¯å£å¤´äº¤é™…ä½¿ç”¨çš„è¯è¨€ã€‚åœ¨å¤–è¯çš„å¦ä¹ è¿‡ç¨‹ä¸ï¼Œå£è¯è¯¾ç¨‹æ˜¯éžå¸¸é‡è¦çš„è¯¾ç¨‹ä¹‹ä¸€ã€‚å¦ä¹ æ±‰è¯ä¹Ÿç¦»ä¸å¼€æ±‰è¯å£è¯çš„å¦ä¹ ã€‚äººä»¬çš„å£è¯èƒ½åŠ›å¾€å¾€ä¼šå½±å“åˆ°äººä¸Žäººä¹‹é—´çš„å®žé™…äº¤é™…çŠ¶å†µã€‚ç¬”è€…åœ¨èµ¤é“ä½³è‚²ä¸å¦æ•™äº†ä¸€ä¸ªå¦æœŸçš„æ±‰è¯å£è¯è¯¾ç¨‹ä¹‹åŽï¼Œå‘çŽ°æ•™å¦è¿‡ç¨‹ä¸å˜åœ¨å¦ç”Ÿå¦ä¹ æ€åº¦æ¶ˆæžã€å› ä¸ºç¾žæ¶©ã€å…´è¶£ç¼ºå¤±è€Œä¸å–œæ¬¢å¼€å£è¯´æ±‰è¯ç‰é—®é¢˜ã€‚ é’ˆå¯¹è¿™ä¸ªé—®é¢˜ï¼Œè®ºè€…å¯¹èµ¤é“ä½³è‚²ä¸å¦åˆäºŒççš„å¦ç”Ÿä»¥è°ƒæŸ¥é—®å·çš„å½¢å¼è¿›è¡Œäº†è°ƒæŸ¥ï¼Œé€šè¿‡è°ƒæŸ¥ä¹‹åŽç¬”è€…æ€»ç»“äº†äº¤é™…æ³•åœ¨æ±‰è¯å£è¯æ•™å¦è¿‡ç¨‹ä¸çš„ä½¿ç”¨æƒ…å†µã€‚äº¤é™…æ³•æå‡ºæ•™å¦è¿‡ç¨‹å°±æ˜¯äº¤é™…çš„è¿‡ç¨‹ã€‚åœ¨æ•™å¦è¿‡ç¨‹ä¸ï¼Œå¦ç”Ÿå’Œè€å¸ˆä¹‹é—´äº¤æµäº’åŠ¨ï¼Œå¯ä»¥æé«˜å¦ç”Ÿçš„å¦ä¹ å…´è¶£ã€‚æ ¹æ®è°ƒæŸ¥å‘çŽ°ï¼Œäº¤é™…æ³•çš„ä½¿ç”¨å¯ä»¥åœ¨ä¸€å®šç¨‹åº¦ä¸Šæé«˜æ±‰è¯çš„æ•™å¦æ•ˆæžœã€‚ å…³é”®è¯ï¼šäº¤é™…ï¼›äº¤é™…æ³•ï¼›æ±‰è¯å£è¯ Abstract : Spoken language is used in oral communication. To study foreign language,spoken language is one of the most important courses. The study of Chinese spoken language also can not be separated from Chinese language learning. Peopleâ€™s speaking ability will do affect on the communication situation between us. After the author had taught oral Chinese spoken for a term in the Bumi Khatulistiwa Middle School. Find the problems that the students all have a negative attitude, and do not like to speak Chinese out, because of their shyness and lacking of interests. To solve the problems, the author surveys the students in the form of questionnaire survey. To conclude the using of communicative approach in the teaching of spoken Chinese. The communicative approach point out that teaching process is the process of communication. In the course of teaching, the teacher and students communicate each other, can improve the students learning interest. According to the survey, it is found that the using of communicative approach can improve the teaching effect in a certain extent on the teaching of spoken Chinese. Key words: Communication; Communicative approach; Spoken Chinese Â